2017
DOI: 10.1108/ijrdm-05-2016-0076
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating the brand-customer relationship in Facebook fan pages

Abstract: Structured Abstract: PurposeThe study is to examine determinants of continuous brand-customer relationship via company-hosted SNSs (social networking sites). Factors that influence fans to continue using fast-fashion brands' Facebook fan pages and to maintain the brand-customer relationship are firstly discussed. Subsequently, predictors of fans' engagement and affective commitment to a fast-fashion brand are examined with aim to explore key elements which nurture brand-customer relationship via brands' SNSs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 89 publications
1
30
0
Order By: Relevance
“…Accordingly, a study by Leckie et al (2016) shows that consumer engagement is central to brands since consumers take an active part to co-create their own experiences via interactions with brands. In the same vein, a recent study by Chang et al (2017) also demonstrated that engagement influences continued intention to use in the fast-fashion industry. Their finding shows that engagement with the brand is deemed as an indispensable ingredient for the lasting brand-customer relationship (Chang et al, 2017).…”
Section: Development Of Brand Loyaltymentioning
confidence: 86%
See 1 more Smart Citation
“…Accordingly, a study by Leckie et al (2016) shows that consumer engagement is central to brands since consumers take an active part to co-create their own experiences via interactions with brands. In the same vein, a recent study by Chang et al (2017) also demonstrated that engagement influences continued intention to use in the fast-fashion industry. Their finding shows that engagement with the brand is deemed as an indispensable ingredient for the lasting brand-customer relationship (Chang et al, 2017).…”
Section: Development Of Brand Loyaltymentioning
confidence: 86%
“…In the same vein, a recent study by Chang et al (2017) also demonstrated that engagement influences continued intention to use in the fast-fashion industry. Their finding shows that engagement with the brand is deemed as an indispensable ingredient for the lasting brand-customer relationship (Chang et al, 2017). Brodie et al (2011) investigated consumer engagement in a virtual brand community and noted that the consumers who interact with the brand showed their loyalty to the brand by recommending the brand to others.…”
Section: Development Of Brand Loyaltymentioning
confidence: 86%
“…The relationship congruency and content on social network sites to consumer click ads and comment about companies (Chang and Fan, 2017). Especially, fan page can give rise to hedonic consumption through fan sites (Turel et al, 2010).…”
Section: Congruitymentioning
confidence: 99%
“…Since the e-word-of-mouth communication might positively influence the building and maintenance of brand-customer relationships for fast fashion brands in terms of long-lasting relationships between consumers and fast fashion brands (Chang and Fan, 2017), our findings provide a measure of these relationships, while the high number of positive tweets indicates positive comments-experiencesopinions. Our findings also have practical implications for the fast fashion industry, which is characterized by the need to reply quickly to consumers' demands for new products with the help of superior decision support systems (Choi et al, 2014;Cook and Yurchisin, 2017), by helping retailers in this sector in access in real time information on consumers' trends and respond rapidly.…”
Section: Resultsmentioning
confidence: 95%
“…Summarizing, the challenges of fast fashion retailers are: (i) efficient just-in-time models (the delivery of goods to meet consumers demand with minimal inventory at the store), (ii) agile supply chains (shorter and more flexible demand driven supply chains), (iii) quick response (to consumer needs with new and fast available products), and (iv) demand chains (supply chains focused on customers' requirements) (Barnes and Lea-Grenwood, 2010;Zhang et al, 2017). Moreover, word-of-mouth communication (with emphasis on e-word-of-mouth), celebrity endorsement, new forms of advertising, with emphasis on social media like Facebook can positively influence the building and maintenance of brand-customer relationships for fast fashion brands, due to the positive effect of engagement and affective commitment facilitated by the social media (Barnes and Lea-Greenwood, 2010;Chang and Fan, 2017;Halvorsen et al, 2013). In particular, those two factors are considered as determinants of long-lasting relationships between consumers and fast fashion brands (Chang and Fan, 2017).…”
Section: Theoretical Background 21 Fast Fashion and Consumer Behaviormentioning
confidence: 99%